Treatment approach for primary hyperparathyroidism in pregnancy - Latif, Azka (Proc (Bayl Univ Med Cent), 2020)
Primary hyperparathyroidism is rare in pregnancy, with an incidence of 1%. It is associated with maternal, fetal, and neonatal complications. Herein, we present two patients with gestational primary hyperparathyroidism who failed medical management and underwent successful parathyroidectomy. Based on our experience and review of the literature, gestational hyperparathyroidism appears to be a clear indication for early parathyroidectomy in both symptomatic and asymptomatic patients.